2017
DOI: 10.1038/srep42775
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Expression Pattern of Human Overlapping lncRNA and Protein-coding Gene Pairs

Abstract: Long non-coding RNA overlapping with protein-coding gene (lncRNA-coding pair) is a special type of overlapping genes. Protein-coding overlapping genes have been well studied and increasing attention has been paid to lncRNAs. By studying lncRNA-coding pairs in human genome, we showed that lncRNA-coding pairs were more likely to be generated by overprinting and retaining genes in lncRNA-coding pairs were given higher priority than non-overlapping genes. Besides, the preference of overlapping configurations prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 57 publications
3
34
0
1
Order By: Relevance
“…Among more than 3,000 miRNAs [90] and 24,793 annotated lncRNAs that have been identified within the human genome [91], only a few show deregulations in cutaneous melanoma (Table 1). Nevertheless, we are only at the beginning of our understanding and identification of ncRNAs; recent computational analyses using high-throughput expression data, including microarrays and RNA sequencing, have helped us identify deregulated mRNAs, lncRNAs and pseudogenes in melanoma [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Among more than 3,000 miRNAs [90] and 24,793 annotated lncRNAs that have been identified within the human genome [91], only a few show deregulations in cutaneous melanoma (Table 1). Nevertheless, we are only at the beginning of our understanding and identification of ncRNAs; recent computational analyses using high-throughput expression data, including microarrays and RNA sequencing, have helped us identify deregulated mRNAs, lncRNAs and pseudogenes in melanoma [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…The observation in early computational experiments that antisense transcripts show splicing differences and often minimal sequence identity between closely related species argued against stringent conservation ( Veeramachaneni et al, 2004 ; Wood et al, 2013 ). However, recent reports based on microarray or RNAseq data, taking conserved transcription or expression patterns into account, confirm phylogenetic conservation of antisense transcription ( Ling et al, 2013 ; Hezroni et al, 2015 ; Ning et al, 2017 ).…”
Section: Functional Relevance Of Natsmentioning
confidence: 97%
“…Secondly, the complementary sense and antisense transcripts can hybridize and form a dsRNA intermediate ( Figure 2A ). This interaction potentially interferes with the processing of both RNAs, their splicing, nuclear export or even translation ( Hastings et al, 2000 ; Ning et al, 2017 ). Alternatively, dsRNA is recognized by enzymes that resolve the double-strand structure and trigger various cellular responses ( Wang and Carmichael, 2004 ).…”
Section: Mechanisms Of Antisense Regulationmentioning
confidence: 99%
“…When portions of lncRNAs overlap a coding gene, it is expected that this region be conserved and under a strong selective pressure. A recent study found that the evolutionary age, overlapping configuration, and local genomic environment of an lncRNA-coding gene pair influence the expression correlation of the pair [ 96 ]. While there needs to be further research of lncRNA-coding pairs in more well-annotated genomes, it is clear that positional information is important in understanding their functional relationship.…”
Section: Discovery Prioritization and Validation Of Lncrnasmentioning
confidence: 99%